Student-Faculty Lunch Program to Increase Mentoring and Facilitate Cross-Program Relationships in School of Nursing. Issue 3 (May 2016) - Lewinski, Allison; Wainwright, Kristin; Gordon, Helen; Derouin, Anne
Abstract : Let's DU Lunch is a pilot program launched to explore the impact of a low-cost, student-faculty lunch program to increase mentoring and facilitate cross-program relationships. This program gave students the opportunity to go to lunch with a faculty member of their choice. A total of 71 students and 25 faculty participated. This program provided the opportunity for positive student-faculty interaction and mentoring and facilitated cross-program relationships.